Secured File Storage in Cloud Computing Application: Secura-Drive - Nair, Nidhi; Jain, Tanuj; Gada, Mihir (2021 12th International Conference on Computing Communication and Networking Technologies (ICCCNT), 2021)
In the current digitizing world, storing our important documents or records on a cloud storage service has become an efficient method but storage drives can be vulnerable if not secured properly. This persuaded us to implement a secure drive that will value the highly rated motto of furtiveness which is the most desired principle in today's era. In this paper, we outlined a solution to overcome the problem of unauthorized user's access to the contents of the database by storing the files in the database in an encrypted format that will maintain the integrity of the data. A comparative study was constructed by analyzing three different cryptographic algorithms based on the security provided and the time required of encrypting-decrypting the file. Based on the comparison, the best technique was used in the cloud storage application. The drive will be immune to attacks and penetrations using encryption and two-step authentication using Face ID Authorization. To use the drive economically, the solution was to compress the files before storing them. The files selected for upload by the user will be compressed and encrypted at the client-side before uploading and decrypted and decompressed back in the original size after the user requests to view it.